Direct Gaze Blurs Self-Other Boundaries. Issue 3 (3rd July 2018) - Zhou, Chu; Jiang, Tianjiao; Zhu, Lei
Abstract: Self-other merging can arise not only between acquainted people but also between strangers. To date, the factors determining self-other merging between strangers remain to be elucidated. We investigate whether strangers' facial appearance (i.e. gaze direction) modulates such initial processes of self-other merging. In the two experiments, participants viewed strangers' faces whose gaze either directed to or averted from them. The extent of self-other merging was measured in terms of perception of face resemblance, Inclusion of the Other in the Self (IOS) scale, and correlations of personality judgments. We found that direct gaze blurred the self-other boundaries at both facial and conceptual levels. Participants felt a stranger who directly gazed at them to be closer and more similar to themselves about face and personality.